Phonological awareness: influences and associates in the context of the development of word reading in young children - Gibbs, Simon James Colville (1997)
This thesis sets out to investigate aspects of the development of phonological awareness in relation to word reading in children aged between 5- and 7-years. The principal aim has been to establish how, for these children, phonological awareness relates to other cognitive factors that might jointly support the development of early reading skills. Data derives from children in their first three years of formal education (aged 5- to 7-years) and a group of partially-hearing children aged 7-years.